KADAR LEMAK DAN PROTEIN DAGING BURUNG MERPATI LOKAL (Columba livia) YANG DIPELIHARA SECARA INTENSIF DAN DIPOTONG PADA UMUR BERBEDA - Raga Samudera; Siti Dharmawati; Said Prasetiyo (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
The research was aim at study and give information of crude protein and fat of local pigeon meat (Columba livia) that was slaughtered at different age and intensive care system. The research used completely randomized design, with five treatments and four replications. If any significant effects found. Further analysis was conducted using Duncan’s Multiple Range Test (DMRT). Treatments set out for this research was selection of local pigeon at the different ages : M3 (3 weeks), M4 (4 weeks), M5 (5 weeks), M6 (6 weeks), M7 (>4 months) there were 4 pigeons for each sample. Variables observed were crude protein and fat of meats. Result of this research is the local pigeon that slaughtered in different age is significantly (P<0,01) to protein level of the meats of local pigeons in intensive  care system. Keywords: local pigeon, intensive care system, crude protein, fat